The Effect of Income Smoothing and Procyclicality Behavior on the Bank Credit Impairment Losses with IAS 39 Adoption in PSAK 55 as a Moderating Variable - Sparta Sparta; Nadya Trinova (Journal of Economics, Business, and Accountancy Ventura, 2019)
The bank's credit impairment losses play a vital role in maintaining the stability and health of banks, as well as fulfilling the banks' function in channelling public funds. This study aims to determine the effect of income smoothing and the behavior of procyclicality against the banks' credit impairment losses, as well as the role of adoption of IAS 39 in PSAK 55 in moderating the influence of these two variables. The objects of this study are conventional commercial banks, listed on the Indonesia Stock Exchange within the research period of 2008-2017. By using a purposive sampling method, this study obtained 20 bank samples and 196 observations. The hypotheses in this research are tested using multiple regression analysis. This study shows that income smoothing has a positive effect on banks' credit impairment losses, whereas procyclicality and IAS 39 adoption in PSAK 55 does not affect the banks’ credit impairment losses significantly. On the contrary, the adoption of IAS 39 in PSAK 55 weakens the positive effect of income smoothing; however, it cannot moderate the effect of procyclicality on the banks' credit impairment losses. The results of this study have implications for regulators' policies to reduce income smoothing practices, maintain financial system stability because the provision for losses from lowering credit scores is too low, accounting policies stipulated by banks emphasize the interpretation and application of standards, and professional judgment and contradictory policies that can cover deficiencies held by financial accounting standards. Another implication is the need for bank managers to anticipate that by 2020, PSAK adopted from IFRS can be useful.